SU(2)cmb and the cosmological model: angular power spectra - Hahn, Steffen; Hofmann, Ralf; Kramer, Daniel (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Driven by the CMB temperature-redshift (T-z) relation as demanded by deconfining SU(2) Yang-Mills thermodynamics, an according cosmological model is
cmb ist im Titel tiefgestellt
Published: 03 November 2018
Gesehen am 18.06.2019